Employment and Technological Innovation: Evidence from U.K. Manufacturing Firms - Van Reenen, John (Journal of Labor Economics, 1997)
This article uses British firm-level panel data on actual innovative activity drawn from different statistical sources to identify the effect of technical change on jobs. Previous work tends to find positive associations of proxies for technical change and employment, but such studies suffer from various statistical drawbacks. In this study, even when one controls for fixed effects, dynamics, and endogeneity, innovations have a positive and significant effect on employment, which persists over several years. There seems to be little direct role for spillover effects from industry innovations, or any role for industry wages or union power.